Analisis Pengaruh Keadilan Distributif Kompensasi Dan Keadilan Prosedural Kompensasi Terhadap Kinerja Yang Dimediasi Oleh Kepuasan Kerja Pada Karyawan Di Rsud Kraton Kabupaten Pekalongan - Edy, Intan Retno (Jurnal Bisnis Teori & Implementasi)
Â Â This study discusses the organizational justice include distributive justice compensation and procedural justice compensation to employees performance both directly and indirectly influenced by employees satisfaction. The populations in this study were all non medic employees in RSUD Kraton Kabupaten Pekalongan are not served as a Civil Servant totaling 111 people. Data were collected by survey method is to provide a list of questions or questionnaires directly to the respondent. Data analysis techniques in this study using analysis of SEM (Structural Equation Modeling) program operated through AMOS 21. The results showed that distributive justice compensation significant positive effect on employees satisfaction, procedural justice compensation significant positive effect on employees satisfaction, distributive justice compensation are not significantly to employees performance, procedural justice compensation are not significantly to employees performance, employees satisfaction significant positive effect on employees performance. Employeesâ satisfactions as a mediating influence of distributive justice compensation and procedural justice compensation to employees performance.